How do you solve -2(6x+3)=-27–5x ?

QUESTION POSTED AT 02/12/2019 - 07:56 AM

Answered by answersmine AT 02/12/2019 - 07:56 AM

Hi!

Our goal is to isolate x on one side by doing the same operation on both sides.

First let's use the distribution property.
-2 x 6 = -12
-2 x 3 = -6
-12x - 6 = -27 - 5x

Add 6 to both sides
-12x - 6 + 6 = -27 + 6 - 5x
-12x = -21 - 5x

Add 5x to both sides
-12x + 5x = -21 - 5x + 5x
-7x = -21

Divide by -7 on both sides
-7x/-7 = -21/-7
x = 3

The answer is x = 3

Hope this helps! :)
Post your answer

Related questions